The Effectiveness Of A Concrete Media Assisted Project Based Learning Model On Students 'Science Competency - Pratiwi, Ni Wayan Aprillia; Manuaba, Ida Bagus Surya (Universitas Pendidikan Ganesha, 2020)
This study aimed to determine the effect of project based learning model assisted by concrete media toward the competency of science among students grade V SD Academic year 2019/2020. A quasi-experiment was used in this study with the nonequivalent control group design. The total number of students in grade V SD Academic Year 2019/2020 was 13 classes consisting of 371 students used as the study population. Random sampling was used to select the samples. The experimental group in this study was the grade VBÂ with 32 students, and the control group was students grade VA with 33 students. Data of science knowledge competency was collected using an objective test instrument in multiple-choice totaling 31 items validated. The science competency data was then analyzed by performing the variant polled t-test. Based on the results of the t-test, tcount = 4.17. The score was then compared with the score of table with df = 63. With a significance level of 5% so that the score of table = 2,000 means that Ho was rejected, because tcount = 4.17> ttable = 2,000. Similarly, the average science competency among students in the experimental group x Ì… = 81.43> x Ì… = 70.33 the average of scientific competence of the control group students. The conclusion obtained from this study is that the Project Based Learning model assisted by concrete media significantly influences students' scientific competence grade V SD Academic Year 2019/2020.